Digital Literacy Skills of Teachers in Elementary School in The Revolution 4.0 - Lestari, Hana; Siskandar, Ridwan; Rahmawati, Ima (International Conference on Elementary Education, 2020)
Digital literacy is an ability to acquire, understand and use information derived from various sources in digital. Along with the rapid development of information and communication technology in the revolution 4.0, the government requires teachers in schools through the national literacy movement, teachers are required to not only be able to use digital technology but also to assess the validity of information obtained from digital sources. The purpose of this research to know the information literacy skills of teachers in elementary school. This research used a qualitative research design descriptive. The sampling method is a stratified random sampling technique in 104 teachers from 5 elementary schools in Bogor. The results of this study indicate the level of digital literacy among elementary schools teachers in the city of Bogor is already middle in all aspects of competence, both on internet searching aspects, hypertextual navigation aspects, content evaluation aspects, and knowledge assembly aspect